The arsonist - Oakes, Stephanie (Young adult author) (Dial Books, 2017)
Molly Mavity and Pepper Yusef are dealing with their own personal tragedies when they are tasked by an anonymous person with solving the decades-old murder of Ava Dryman, an East German teenager whose diary was published after her death.